Searching for meanings: a critical-reflexive analysis of entrepreneurship appropriation in small Brazilian towns - Valadares, Josiel Lopes; Macedo, Suélem Viana; de Melo, James Rocha Rodrigues (Revista Eletrônica de Administração, 2022)
This research aims to develop a critical-reflexive analysis of entrepreneurship in public management based on two significant works of Alberto Guerreiro Ramos: ‘The sociological reduction’ and ‘The new science of organizations.’ The research is qualitative, based on bibliographic, documentary data, in-depth interviews, online questionnaires, and direct observation. The results show that the challenges present in the context of study indicate that small municipalities can present fertile ground for the development of entrepreneurial practices. The analyses have also shown that the main deficiencies of the small towns are the managers’ lack of training, the lack of effective articulation with the federal level, the lack of an environment capable of fostering proactivity and participation, the financial crisis, and the necessary behaviors and arrangements. A huge gap for the development of effective businesss practice is the loose coordination of the Union, states and municipalities, which is a historical feature of the country.